Expressing MicroRNA Bantam Sponge Drastically Improves the Insecticidal Activity of Baculovirus via Increasing the Level of Ecdysteroid Hormone in Spodoptera exigua Larvae - Ran, Zihan; Shi, Xiaojie; Han, Fangting; Li, Jianbei; Zhang, Youyi; Zhou, Yanjun; Yin, Juan; Li, Rui; Zhong, Jiang (Frontiers in Microbiology, 2018)
Bantam is a conserved miRNA highly expressed in insects. We previously showed that the antisense inhibitor (antagomiR) of bantam improved the infection by baculovirus Autographa californica nucleopolyhedrovirus (AcMNPV) in Spodoptera exigua and S. litura larvae. Here, we constructed a recombinant AcMNPV (vPH-banS) expressing bantam sponge, an mRNA containing eight antisense binding sites for bantam. Infection with wild type AcMNPV (WT) or the control recombinant virus vPH resulted in a significant increase of bantam level, whereas infection with vPH-banS led to an approximately 40% reduction of bantam in both Sf9 cells and S. exigua larvae. Although comparable production of budded virus and polyhedra were detected in vPH-banS-, vPH-, and WT-infected Sf9 cells, vPH-banS showed remarkably increased insecticidal activity in S. exigua larvae. The 50% lethal concentration and the median lethal time of vPH-banS was only 1/40 and 1/2, respectively, of both vPH and WT. Further analysis showed that the level of molting hormone 20-hydroxyecdysone (20E) was significantly higher in larvae infected by with vPH-banS than those infected by with vPH or WT. This was confirmed by the result that the larvae treated with bantam inhibitor also had a markedly increased 20E level. Moreover, feeding larvae with 20E increased the virus-mediated mortality, whereas feeding with juvenile hormone partially reverted the high insecticidal effect of vPH-banS. Together, our results revealed that vPH-banS infection suppresses the level of bantam, and in turn elevates level of 20E in infected insects, resulting in increased susceptibility to baculovirus infection. Our study provided a novel approach to improve a baculovirus bio-insecticide by interfering with a key homeostasis-regulating miRNAs of the host.